SURVEI GEOLISTRIK UNTUK MENGETAHUI POTENSI AIR TANAH DI KEPULAUAN AYAU, KABUPATEN RAJA AMPAT, PROVINSI PAPUA BARAT: GEOELECTRIC SURVEY TO KNOW THE POTENTIAL OF GROUNDWATER IN AYAU ISLANDS, RAJA AMPAT REGENCY, WEST PAPUA PROVINCE - Khristian Enggar Pamuji (JISTECH: Journal of Information Science and Technology, 2014)
Geoelectricity survey has been done in Ayau Islands, Raja Ampat Regency, West Papua Province. The measurement method that used is sounding, whereas electrode configuration used is Schlumberger configuration with a stretch of 100 -150 m. The data obtained are then processed by Progress Software. The results of this survey obtained show that in the geoelectricity sounding measurement point not found any good groundwater aquifers, as the water source of drilled well. Water layer with the thickness between 1-3 m at the surface (alluvial) is a rain water infiltration that is not recommended to make boreholes at this point.